AGREE II assessments of recent acne treatment guidelines: how well do they reveal trustworthiness as defined by the U.S. Institute of Medicine criteria?. (1st December 2017) - Eady, E.A.; Layton, A.M.; Sprakel, J.; Arents, B.W.M.; Fedorowicz, Z.; van Zuuren, E.J.
Summary: Background Up‐to‐date, trustworthy guidelines are a widely relied upon means of promoting excellent patient care. Objectives To determine the quality of recently published acne treatment guidelines by utilizing the Appraisal of Guidelines for Research and Evaluation (AGREE) II Reporting Checklist, the U.S. Institute of Medicine's (IOM) criteria of trustworthiness, the red flags of Lenzer et al . and CheckUp. Methods Systematic searches were conducted in bibliographic databases, guideline depositories and using Google to identify acne treatment guidelines published since 2013. Six assessors independently scored each guideline using the AGREE II Reporting Checklist. Guidelines were concomitantly assessed for trustworthiness using the IOM criteria and for the red flags of Lenzer et al ., indicative of potential bias. Updates were screened using CheckUp. Results Eight guidelines were identified, two of which were updates. Lowest scoring AGREE II domains across all guidelines were applicability (six poor, one fair, one average) and rigour (four poor, one fair, three average). Two of the three highest‐scoring guidelines were developed using AGREE II. No guideline fully met each IOM criterion and all raised at least one red flag indicative of potential bias. One updated guideline did not address seven of 16 items on CheckUp and the other did not address four. Patient involvement in guideline development was minimal. Conclusions Use of the AGREE II instrument during guideline development did not have as great an effect on guideline quality as might be expected. There is considerable room for improvement in acne treatment guidelines in order to satisfy the IOM trustworthiness criteria and avoid bias.